A prospective study to assess the social stigma, perceived stress and psychological distress among security guards during COVID-19 pandemic in All India Institute of Medical Sciences, New Delhi - Ahlawat, Sheenu; Joshi, Poonam; Susaimuthu, Cecilia Mary; Goel, Prabudh; Lodha, Rakesh; Jain, Vishesh; Sharan, Pratap (International Journal Of Community Medicine And Public Health, 2021)
Background: People working in the health sector were being labelled, stereotyped, discriminated against, stigmatized, and treated indifferently in the early phase of coronavirus disease 2019 (COVID-19) pandemic. To assess social stigma, perceived stress, and psychological distress among hospital security guards during the COVID-19 pandemic. Methods: A prospective study was conducted among security guards, working in a tertiary care health facility, during the early part of the COVID-19 pandemic. The data were collected using an online Google form. The stigma, perceived stress, and psychological distress were assessed using standardized tools. Results: The mean age of 280 (males: 219, 78.2%) guards enrolled in the study was 37.13±9.1 years. The mean stigma, stress, and psychological distress scores among security guards were 28.76±11.9, 17.64±6.4, and 4.35±2.8, respectively. A significant correlation was found between perceived stigma and psychological distress (r=0.197, p=0.009) and perceived stress and psychological distress (r=0.302, p=0.001). The predictor of perceived stress among the security guards were gender, [β=1.88; (1.13, 2.63), p=0.001] and loss of job by the family member during pandemic [β=2.8 (4.56, 1.03), p=0.001], similarly the predictors of psychological distress were gender and COVID positive status [β=0.06 (0.10, 0.33), p=0.001]. Conclusions: The majority of the security guards had moderate to high perceived social stigma, and moderate level stress during the COVID-19 Pandemic and a few being psychologically distressed requiring referral to experts.